2015
DOI: 10.1155/2015/820764
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology and Growth of Anodic Titania Nanotubes Films: Photoelectrochemical Water Splitting Studies

Abstract: Design and development of one-dimensional nanoarchitecture titania (TiO) assemblies have gained significant scientific interest, which have become the most studied material as they exhibit promising functional properties. In the present study, anodic TiO2films with different surface morphologies can be synthesized in an organic electrolyte of ethylene glycol (EG) by controlling an optimum content of ammonium fluoride (NH4F) using electrochemical anodization technique. Based on the results obtained, well-aligne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Raman spectroscopy is a more effective technique than XRD in revealing structure transitions of the complex WO x system, as Raman spectroscopy has higher sensitivity to changes in the positions of and bonding between the W and O atoms in the crystal lattice, while with XRD it is often difficult to distinguish the similar and often overlapping diffraction peaks. Using Raman spectroscopy, Lai [17] has investigated the structural change of WO 3 nanoplatelet films containing different amounts of ammonium fluoride and related it to the photocatalytic properties. Lu et al [18] have reported the oxidation and phase transition of sub-stoichiometric W 18 O 49 nanowires using intrinsic Raman spectroscopy by changing the input laser power.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is a more effective technique than XRD in revealing structure transitions of the complex WO x system, as Raman spectroscopy has higher sensitivity to changes in the positions of and bonding between the W and O atoms in the crystal lattice, while with XRD it is often difficult to distinguish the similar and often overlapping diffraction peaks. Using Raman spectroscopy, Lai [17] has investigated the structural change of WO 3 nanoplatelet films containing different amounts of ammonium fluoride and related it to the photocatalytic properties. Lu et al [18] have reported the oxidation and phase transition of sub-stoichiometric W 18 O 49 nanowires using intrinsic Raman spectroscopy by changing the input laser power.…”
Section: Introductionmentioning
confidence: 99%
“…The pores grow into tubular features and form TNT arrays as the anodizing process continues to its final stage (Figure 12c,d). The growth of TNT arrays is described as the competition between electrochemical oxide formation and chemical dissolution of oxide by F − ions of sufficient concentrations [222][223][224]. Figure 13a,b shows the formation of TNT arrays by anodizing Ti in a mixed ethylene glycol/NH 4 F and water solution [223,225].…”
Section: Electrochemical Anodizationmentioning
confidence: 99%
“…Fabricating nanostructures with good alignment and uniform size to actualize most of the proposed applications by the conventional lithographic process was even more difficult [ 6 ]. Various experiments have been conducted to create porous materials using naturally occurring materials or self-organizing materials such as carbonates [ 7 , 8 , 9 , 10 , 11 ]. Porous anodic alumina membranes (PAAMs), which are incredibly porous and have specified shapes and sizes, are one sort of ordered porous structure [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%